2018
DOI: 10.5500/wjt.v8.i4.102
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation in older recipients: Preemptive high KDPI kidney vs lower KDPI kidney after varying dialysis vintage

Abstract: AIMTo evaluate the outcomes of transplanting marginal kidneys preemptively compared to better-quality kidneys after varying dialysis vintage in older recipients.METHODSUsing OPTN/United Network for Organ Sharing database from 2001-2015, we identified deceased donor kidney (DDK) transplant recipients > 60 years of age who either underwent preemptive transplantation of kidneys with kidney donor profile index (KDPI) ≥ 85% (marginal kidneys) or received kidneys with KDPI of 35%-84% (better quality kidneys that old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Dialysis duration has been suggested as the strongest independent modifiable risk factor for kidney transplant recipients because of its association with increased comorbidity burden, immunological alterations, and physiological reserve decline in recipients. 5 , 22 Meanwhile, longer hospital stay after transplant has been attributed to the disease status of the recipient and the organ. 6 Prolonged transplant admission, therefore, is likely a reflection of a high-risk recipient who is prone to adverse outcomes such as early readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…Dialysis duration has been suggested as the strongest independent modifiable risk factor for kidney transplant recipients because of its association with increased comorbidity burden, immunological alterations, and physiological reserve decline in recipients. 5 , 22 Meanwhile, longer hospital stay after transplant has been attributed to the disease status of the recipient and the organ. 6 Prolonged transplant admission, therefore, is likely a reflection of a high-risk recipient who is prone to adverse outcomes such as early readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…Tullius et al 27 established that the risk of rejection in allografts from older donors is attenuated in older recipients—a benefit likely afforded through immunosenescence—whereas separate US studies have suggested that preemptive transplantation, in minimizing the accrued morbidity of dialysis, may offset risks associated with high-KDPI allografts in older recipients. 25,28…”
Section: Discussionmentioning
confidence: 99%
“…Beyond specific donor circumstances, these discussions may be moderated by multiple factors, including avoidance of antibodies in sensitized patients, likelihood of future offers, and potential morbidity of remaining on dialysis. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Preemptive Kidney Transplantation (PKT) is defined as Kidney Transplantation (KT) before starting chronic dialysis [1,2]. Chances of receiving PKT are more likely with the availability of living kidney donors, but only one third of the Living Donor Kidney Transplantations (LDKT) currently receives PKT [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Preemptive Kidney Transplantation (PKT) is defined as Kidney Transplantation (KT) before starting chronic dialysis [1,2]. Chances of receiving PKT are more likely with the availability of living kidney donors, but only one third of the Living Donor Kidney Transplantations (LDKT) currently receives PKT [1][2][3]. These shortcomings in the progress of PKT could be principally attributed to delayed referral of patients to transplantation centers and a few unfavourable concerns about PKT [3][4][5].…”
Section: Introductionmentioning
confidence: 99%